An investigation into the prevalence and impact of breast pain, bra issues and breast size on female horse riders - Burbage, J.; Cameron, L. (Journal of Sports Sciences, 2017)
For female horse riders, breast pain, bra issues and breast size may be important concerns which have yet to be considered. This study aimed to establish the prevalence of breast pain and bra issues in female horse riders and explores the impact of breast size on breast pain and bra issues. A 6-part, 32 question online survey was completed by 1324 females who participated in horse riding activities. Descriptive and chi-squared (?2) analyses were utilised; data for 1265 participants were included in the final analysis. Breast pain was experienced by 40% of all participants and this was significantly related to self-reported cup size (?2 = 54.825, P < 0.001), increasing linearly. Breast pain was experienced most frequently during sitting trot and 21% of symptomatic participants reported that breast pain affected their horse riding performance. At least one bra issue was reported by 59% of participants; larger-breasted participants reported experiencing all bra issues more frequently than smaller-breasted participants (P < 0.001). These results demonstrate that educational initiatives are needed to ensure female horse riders are informed about appropriate bra fit and breast support during horse riding to increase comfort and help reduce the potential negative associations with performance